GW approximation study of compton profiles of some transition metal oxides and semiconductors / Sidiq Mohamad Khidzir - Sidiq , Mohamad Khidzir (2018)
Ground state Density Functional Theory (DFT) calculations via the Localized Density Approximation (LDA) functional has shortcomings in explaining experimental Compton profiles, typically seen in disagreement of the lower momenta regions as a result of an incomplete description of correlation effects. In constructing the momentum densities via the LDA functional, which will subsequently be used to construct the Compton profiles, the input required is the occupation number density which is dependent on the initialized state. Obtaining the band structure, we can confirm the largest contributing orbitals to the momentum density. Knowledge of the contributing orbital states alone is inadequate to completely explain the shortcomings behind the LDA momentum density. Using the GW (Green's function-Dielectric screening) Approximation, the momentum density is constructed from the spectral function which is a Lorentzian as a function of self-energy. This self-energy term itself is dependent on the dielectric screening term. In this work, Compton profiles constructed via the GW Approximation will be shown to provide not only greater insight via the dielectric screening and self-energy terms, it will also provide better agreement to experiment compared to the LDA Compton profiles. In our study of NiO, we observe that the sum of absolute values of the difference profiles is smaller in the case of GWA compared to LDA indicating generally better agreement. For TiO2, we observe that the GWA reproduces a smaller difference profile at higher momenta compared to LDA. To further investigate the well known strongly correlated system NiO, we have compared it to other Mott insulators FeO and CoO. We observe that NiO has twice broadened spectral functions compared to FeO and CoO. This has been attributed to the twice larger dorbital contribution as observed in the partial density of states. The NiO momentum density is more occupied in the low momentum region compared to FeO and CoO and this confirms the role of NiO as a strongly correlated system. The amplitude of the anisotropy of NiO is seen to be larger than FeO and CoO. This is attributed to asymmetry of valence electron profiles induced by spectral functions and vertex corrections. In our study of ZnSe, we observe between 0-1.5 a.u, there is better agreement to the previous study via the GWA difference profile compared to the LDA difference profile.